Supervisi Pendidikan Sebagai Instrumen Peningkatan Kualitas dan Profesionalitas Guru Dalam Pembelajaran - Eferadina Salsabila Novariantry; Nazilla Nur Febriani; Wiwin Luqna Hunaida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational supervision is one of the crucial approaches in improving the quality of learning and the professionalism of educators. Supervision not only functions as a form of supervision but also includes coaching, mentoring, and providing professional support for educators. This article aims to examine the concept of educational supervision as a whole, including the definition, function, role of supervisors, effective supervision strategies, and its advantages and disadvantages. This research uses a literature study method with a content analysis and descriptive approach to various relevant literature sources. The results of the study indicate that supervision carried out with the right strategy, such as a collaborative, reflective, data-based approach, and effective communication is able to encourage continuous improvement in the quality of learning and educator competence. However, educational supervision also faces various challenges, such as limited supervisor capabilities, inappropriate approaches, and excessive focus on administrative aspects. Therefore, the implementation of appropriate and systematic supervision is needed to create a conducive learning environment and support the professional development of educators.